Enhancing Learning Outcomes and Creative Thinking through Project-Based Learning Modules in Fourth Grades - Tio Gusti Satria; Sapriya Sapriya; Udin Syaefudin Sa’ud; Cepi Riyana; Tri Syamsijulianto; Joni Helandri (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
The study aimed to determine the improvement of learning outcomes and creative thinking through project-based learning modules in fourth graders. The research method used was a pre-experimental design with a one-group pretest-posttest design. The research subjects were fourth-grade students from an Islamic elementary school in Lubuklinggau city with a population of as many as two classes with a random sampling technique and obtained class IVA. The research instrument used was an objective test consisting of 10 essay questions with material on cultural diversity, local wisdom, history, and culture, and rubrics to assess students' creative thinking skills, including fluency, flexibility, originality, and elaboration. Based on the hypothesis testing on the cognitive aspect of learning outcomes using the t-test, it shows a significant impact on students' learning outcomes in classes that use project-based learning models in IPAS learning with an increase in the difference score of 24.77. Creative thinking skills, assessed based on the rubric for assessing students' creative thinking skills, showed that there was a significant development of student's creative thinking skills in classes that used a significant project-based learning model with an increase in the difference score of 17.32, at the basic stages of development that occurred in the preparation, implementation, and presentation of results from not creative (level 1) to creative (level 2). The implications of this study extend to future research to support the improvement of students' learning outcomes and creative thinking skills.